The Contingent Fit between Management Control System and Capabilities on Sustainability Performance - Rosini, Iin; Gunawan, Juniati; Hakim, Dani Rahman (International Journal of Business, Economics and Management, 2020)
This study aims to analyze the contingent fit between the management control system (MCS) with capabilities to improve the company's sustainability performance. The final sample was 185 environmental managers, human resources, marketing, operational, and corporate social responsibility (CSR) managers from 45 listed companies on the Indonesia Stock Exchange that published the annual report. Primary research data were taken by questionnaire. The data analysis method uses structural equation models with the help of the Smart PLS application. The results of this study indicate that 1) MCS has a direct effect on sustainability performance. 2) MCS affects capability. 3) Capability influences sustainability performance, and 4) contingent fit between MCS and capability has a proven impact on sustainability performance. Based on these results, future studies are expected to focus not only on the influence of MCS and capabilities on sustainability performance but also on the contingent fit between MCS and these capabilities. Thus, companies need to use MCS that has a contingent fit with their capabilities to improve sustainability performance.